The Implementation of Legal Certainty Principle in Trademark Law With Regards to the Right of Famous People to Sue Cybersquatter in Indonesia - AMIRULLOH, Muhamad; MUCHTAR, Helitha Novianty; PERMATA, Rika Ratna (Journal of Advanced Research in Law and Economics; Vol 10 No 1 (2019): JARLE Volume X Issue 1(39) Spring 2019DO - 10.14505//jarle.v10.1(39).03, 2019)
The right to sue for famous people whose names or brands are used as internet domain names by cybersquatter has not been regulated in the Law on Trademark in Indonesia. This situation raises questions concerning the certainty of Trademark Law for famous people in claiming for civil compensation against cybersquatters. In this research, This study applies a normative juridical method focusing on the applicable legal provisions, The specification of this research is analytical descriptive, namely, by providing facts about the use of famous trademark names as internet domain names, as well as the right for the famous person to file a claim based on the provisions of the ITE and Trademark Law that can be used as a legal basis for compensation claims against cybersquatters. Results show that the Trademark Law has not yet implemented the principle of legal certainty in protecting famous people who are victims of cybersquatting in Indonesia, particularly in regards to their right to sue for civil compensation, because it did not yet have norms or rules governing the right to claim for civil compensation for famous people whose trademarks (names) are used as domain names by cybersquatters. The concept of regulating trademark in Indonesia needs to include norms or rules regarding the right to sue for civil compensation for famous people who are victims of cybersquatting in Indonesia.